PERANAN WANITA DALAM PERJUANGAN KEMERDEKAAN INDONESIA MASA PENDUDUKAN JEPANG - Wulan Sondarika (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2017)
The purpose of this study is to know the existence of women in Indonesia and the role of women in the struggle for Indonesian independence during the occupation of Japan.The research method used is historical or historical method, with stages; Heuristics, criticism, interpretation and historiography. Data collection techniques used are observation, interview and literature study.The result of the research is that Indonesian women since ancient times especially the Japanese era is very active role. Whether it is active in theorganization or active in social activities.